Kajian Aktivitas Antibakteri Minyak Daun Sereh (Cymbopogon citratus) pada Adonan Sate Lilit Ikan Laut - DewaNyoman Adi Paramartha (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
Lemongrass is one of the spceies often used in cooking or as traditional medicine.The importance components in lemongrass oil that act as antimicrobial is citral. In this research lemongrass oil isolated by steam distilation method and lemongrass oil were tested against Escherichia coli, Staphylococcus aureus, and Salmonella typhi using the agar diffusion method. Antibacterial activity also evaluated on traditional fish satay dough, and tested its organoleptic value. The result showed that lemongrass oil significantly inhibited E. coli with minimum inhibiting concentration (MIC) 0.72 µl/ml and minimum bactericidal concentration (MBC) 2.89 µl/ml, S. typhi with MIC 0.65 µl/ml and MBC 2.59 µl/ml, S. aureus with MIC 0.64 µl/ml and MBC 2.57 µl/ml. Antibacterial activity studies of lemongrass oil as potential food aditive was evaluated by adding highest MIC and MBC value (0.72 and 2.89 µl/g) on traditional fish satay dough. The result showed that adding lemongrass oil 0.72µl/g is not significantly inhibit nature growing bacteria E. coli, Salmonella, and Staphylococcus on satay dough, but adding 2.89 µl/g lemongras oil only can signigicantly inhibit E. coli, Salmnoella, and Staphylococcus at 0 hours of incubation period, but cannot inhibit it’s log phase up to 24 hours of incubation. Organoleptic of added lemongrass oil on fish satay douh was showed that adding 0.72 µl/g of lemongrass oil was not significant on taste and smell, but adding 2.89 µl/g was significant on taste and smell compared to control.